Chinese herbal medicine formula Jieduhuayu granules improves cognitive and neurophysiological functions in patients with cirrhosis who have minimal hepatic encephalopathy: A randomized controlled trial. - Yao, Chun; Huang, Guochu; Wang, Meng; Xia, Meng; Yao, Fan; Niu, Dengfeng; Zhang, Yuer; Li, Shan; Zhong, Yu (Complementary Therapies in Medicine, 2014)
BACKGROUND: Minimal hepatic encephalopathy (MHE) impairs patients' cognitive and neurophysiological functions. In this study, we investigated the effect of treatment-related improvement in cognitive and neurophysiological functions. METHODS: We measured psychometric performance by number connection tests part A (NCT-A), digit symbol test (DST), mini-mental state examination (MMSE) and event related potential P300 wave of 80 patients with cirrhosis who have minimal hepatic encephalopathy on inclusion into the study and 15 days later. They were randomly assigned in a 1:1:1:1 ratio to four groups, to receive treatment of Chinese herbal medicine formula (HMG) or lactulose (LG) or Chinese herbal medicine formula combined with lactulose (HMCLG) for 15 days (n=20) or no treatment (CG) (n=20). This study was not blind. RESULTS: The mean number of NCT-A and MMSE scores improved significantly in patients in the HMG (0 day, 102.00±24.49 for NCT-A, 18.55±2.89 for MMSE; 15 days, 78.30±22.55 for NCT-A, 24.20±2.78 for MMSE) compared with patients in the CG after 15 days of follow-up (0 day, 103.00±24.98 for NCT-A, 17.90±2.99 for MMSE; 15 days, 95.65±24.34 for NCT-A, 18.85±3.12 for MMSE), P<0.05; the mean number of P300 latency (ms) and wave amplitude ([mu]V) improved significantly among patients in the HMG after 15 days of treatment (0 day, 341.90±14.04 for latency, 8.40±1.73 for wave amplitude; 15 days, 305.45±23.95 for latency, 13.00±3.80 for wave amplitude) compared with patients in the CG after 15 days of follow-up (0 day, 343.85±14.88 for latency, 8.29±1.77 for wave amplitude; 15 days, 340.40±13.06 for latency, 8.50±1.82 for wave amplitude), P<0.05. Similar improvement were also found among patients in the LG and HMCLG; improvements among patients in the HMG were significantly greater than they were in the LG (P<0.05). Synergistic action were shown among patients in the HMCLG (P<0.05). CONCLUSION: Treatment with Chinese herbal medicine formula Jieduhuayu granules and lactulose may improve cognitive and neurophysiological functions in patients with cirrhosis who have MHE. Compared with lactulose alone, Chinese herbal medicine formula Jieduhuayu granules has higher efficacy of improving cognitive and neurophysiological functions in patients with cirrhosis who have MHE, and the two of them together show synergistic action. TRIAL REGISTRATION NUMBER: ACTRN12614000193673.